ANALISIS STRATEGI PEMASARAN PADA CORUCA COFEE SHOP KISARAN - Agus Septiyan Kamal Sitorus (Jurnal Niaga & Bisnis (e-journal), 2014)
The purpose of this study was to determine: (1) To identify the marketing strategies undertaken by Coruca Coffee Shop through the analysis of the internal and external environment, (2) Finding alternative marketing strategies that can be used in addressing the problems of Coruca Coffee Shop. The method used in this study is a descriptive study with a qualitative approach. The data and information research consisted of primary and secondary data. The analytical is used a SWOT analysis, matrix IFAS, EFAS matrix, and SWOT matrix. From the analysis of the internal environment is known values ​​of strength (strength) is smaller than the value of weakness (weakness) with a difference of (-) 0,226. While the results of the analysis of the external environment is known the probability to grow is greater than the value of the threat to the difference of (+)0,031. So known position Coruca coffee shop is in quadrant 3. In this condition, a strategy that can be taken is the turnaround strategy with alternative marketing strategies based on SWOT matrix among others: (1) optimize promotions with media that can be use, (2) obtain a business license in order to avoid enforcement of the local government and an opportunity for these businesses to receive additional capital from designated banks to channel credit to small scale businesses, (3) to manage business management, especially with regard to the recording of cash flows Keywords: Bussines competiton, Marketing Strategy, Coruca Coffee Shop, SWOT Analysis, IFAS Matrix, EFAS Matrix, SWOT matrix.